2012
DOI: 10.1007/s00542-012-1456-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of die attachment on key dynamical parameters of micromachined gyroscopes

Abstract: This paper presents the effect of die attachment on the resonant frequency and quality factor of micromachined gyroscopes. Two types of epoxy die attachments are adopted in micromachined gyroscopes. A fourth order mass-spring-damper system is proposed to augment the dynamics of micromachined gyroscopes. Frequency response tests are implemented to analyze the quality factor and resonant frequency. Both maximums of the resonant frequency and quality factor are obviously much larger in the drive mode and sense mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A thermal stress structure was utilized in a cylindrical gyroscope to improve temperature performance in [5], and the open-loop temperature drift rate was reduced by about 2 thirds after the structure was optimized. Two epoxy materials were filled between the structure substrate and package to decrease the quality factor temperature coefficient of the gyroscope in [6], and the temperature coefficient of the drive and sense mode resonant frequencies were 124.1 ppm/°C and −106.9 ppm/°C. In [7], a novel stress compensation method was proposed to assist conventional temperature compensation to improve the long-term drift of MEMS gyroscopes, and a long-term (around 3 hours) test showed that the angle random walk was 0.15°/√h, and bias instability was 1°/h.…”
Section: Introductionmentioning
confidence: 99%
“…A thermal stress structure was utilized in a cylindrical gyroscope to improve temperature performance in [5], and the open-loop temperature drift rate was reduced by about 2 thirds after the structure was optimized. Two epoxy materials were filled between the structure substrate and package to decrease the quality factor temperature coefficient of the gyroscope in [6], and the temperature coefficient of the drive and sense mode resonant frequencies were 124.1 ppm/°C and −106.9 ppm/°C. In [7], a novel stress compensation method was proposed to assist conventional temperature compensation to improve the long-term drift of MEMS gyroscopes, and a long-term (around 3 hours) test showed that the angle random walk was 0.15°/√h, and bias instability was 1°/h.…”
Section: Introductionmentioning
confidence: 99%
“…Due to non-ideal factors, such as manufacturing imperfections and temperature changes, the key parameters of the sensitive structure of the gyroscope will deviate from the ideal design values, and the stability of parameters will significantly impact on the final performance of the gyroscope. The deformation caused by residual stress or thermal mechanical stress is an important problem, because it not only affects the performance [ 7 , 8 , 9 ], but also causes frequency change [ 10 , 11 , 12 ], rigid axis deflection, bias, scale factor drift [ 13 , 14 , 15 ], even breakage of the structure [ 16 ]. The deviation of the operating frequency due to pulling stress is a critical issue, and it should be controlled or eliminated to avoid influencing the gyroscope’s performance [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Imego AB (Gothenburg, Sweden) institute in Sweden and the National University of Defense Technology (NUDT) have carried out a long-term study of the parallelogram oblique beam of BFVG [ 27 , 28 , 29 , 30 ]. The anisotropic wet etching (AWE) process has been adopted in this manufacturing technology process to fabricate the parallelogram oblique beam.…”
Section: Introductionmentioning
confidence: 99%